EMPLOYEE PERFORMANCE REVIEWED FROM LEADERSHIP, COMPETENCE, MOTIVATION AND WORK ENVIRONMENT (Study on The Department of Environment and Forestry Klaten Regency) - Tri Praptama; Istiatin Istiatin; Sudarwati Sudarwati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This research aims to know the influence of a variety of brothers, eras, roots, and work environment outside the variables done by employees in the Office of Environment and Forestry Klaten. Which research is everywhere is quantitative. The life in this study is what all employees in the Klaten District Environment and Forestry Office numbered 43 people. Sampling techniques use saturated samples. The technique for research data analysis is multiple linear regression analysis. The results of which research is done is a variable of a sub-district, era, and work environment has a positive and also good from the variables conducted by employees in the Department of Environment and Forestry Klaten. It is expected that the Klaten District Environment and Forestry Office will continue to maintain and improve the leadership quality, competence, motivation and work environment of existing employees so that the performance of employees will also continue to improve and indeed become better than before. Keywords: Employee Performance, Leadership, Competence, Motivation and Work Environment